A gramática dos pronomes clíticos no Brasil colônia: o português clássico na história do português brasileiro - Cardoso , Lara da Silva (2020)
In this dissertation, I present a discussion on the origins of Brazilian Portuguese, more precisely on which Portuguese grammar was one of the bases of its formation (CASTRO, 1996; GALVES, 2007, RIBEIRO, 2015 [1998]). I discuss the existing proposals on this issue (COHEN, 1997; CUNHA, 1976 [1968]; ELIA, 1979; MEGALE, 1998; MELO, 1971 [1946]; MORAES DE CASTILHO, 2001, 2013; NARO; SCHERRE, 2007; RIBEIRO, 2015 [1998], SILVA NETO, 1976 [1951] inter alia) and argue in favor of Classical Portuguese. To verify this hypothesis, I carry out a linguistic study on the phenomena of interpolation and clitic placement in Brazilian colonial texts representative of the first half of the 17th and 18th centuries – which make up a colonial subcorpus of the Corpus Eletrônico de Documentos Históricos do Sertão (Electronic Corpus of Historical Documents of the Sertão – CE-DOHS). Interpolation consists of the phenomenon of non-adjacency of the clitic pronoun and the verb, due to the presence of constituents between the two terms. Clitic placement, on the other hand, consists of the order of the clitic pronoun in relation to the verb, either in an anterior (proclisis) or a posterior (enclisis) position of the verb – this position being conditioned, throughout the history of Portuguese, by the type of constituent that precedes the verb. The study was carried out based on the assumptions of generative syntax (CHOMSKY, 1986) in the contexts proposed by Namiuti (2008), for the phenomenon of interpolation, and by Galves, Brito and Paixão de Sousa (2005), for the phenomenon of clitic placement. The results confirm the hypothesis about Classical Portuguese as one of the linguistic bases for the formation of Brazilian Portuguese and point out some peculiarities about the use of this grammar in Brazil, such as, for example, a greater frequency of the use of proclisis in variational contexts. Additionally, the analyzed data paved the way for discussions on the phenomenon of interpolation of other elements than não (no/not) in the grammar of Classical Portuguese– used in Portugal and Brazil - and to revisit the course of Portuguese grammars in Brazil, tracing a possible reconstitution of the formation path of the socially prestigious variety of Brazilian Portuguese.